Sittig's handbook of pesticides and agricultural chemicals - Pohanish, Richard P. (William Andrew Publishing, 2015)
This reference handbook provides fully updated chemical, regulatory, health, and safety information on nearly 800 pesticides and other agricultural chemicals. The clear, consistent and comprehensive presentation of information makes Sittig''s an essential reference for a wide audience including first responders, environmental and industrial health/safety professionals, the food industry, the agridcultural sector and toxicologists. Detailed profiles are provided for each substance listed, including: usage; crop-specific residue limits; hazard ratings for long-term human toxicity; endocrine d.